MANAJEMEN RANTAI NILAI KOMODITAS ANGGREK DI PT ANUGERAH ANGGREK NUSANTARA KABUPATEN KEDIRI - Ria, Vina Yunita; Nurmahadi, Brian; Salsabilla, Shafira (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The value chain for the development of orchid commodities at PT Anugerah Anggrek Nusantara has several obstacles, namely the agro-climate that does not support orchid cultivation, low technological innovation, and limited stock availability so that consumer demand cannot be fulfilled optimally. This research was conducted from August to December 2022 at PT Anugerah Anggrek Nusantara Kediri Regency, East Java. Sources of data used, namely primary data through observation, interviews, and documentation, while secondary data through literature studies. The results of the study show that value chain management at PT Anugerah Anggrek Nusantara is carried out with several activities including, procurement of raw material inputs, production processes, and marketing. Procurement of production inputs depends on the activities of the production stages obtained from offline and online stores. Production activities at PT Anugerah Anggrek Nusantara consist of pollination, tissue culture, acclimatization, repotting, maintenance, harvesting and marketing. Marketing activities at this company apply the marketing strategy of the 7P marketing mix, namely product, price, promotion, place, people, process, and physical evidence.